2020
DOI: 10.1186/s41687-020-00246-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and content validation of the Pediatric Oral Medicines Acceptability Questionnaires (P-OMAQ): patient-reported and caregiver-reported outcome measures

Abstract: Background Evolving regulatory guidelines recommend routine assessment of the acceptability of pediatric oral medicines throughout clinical development processes. However, such assessment is problematic owing to a lack of standard methods or criteria that define acceptability for children and their caregivers. This research aimed to identify the attributes of acceptability for targeted oral formulation types that are important to children, and to develop content-valid patient- and caregiver-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Additionally, instruments have been developed to assess patient and/or caregiver acceptability of drug regimens. 23 Palatability as an adherence factor has traditionally focused on pediatric patients, generally in antibiotic development, but research has demonstrated that many of the same acceptability factors that apply to treatments for children also apply to adult patients. 16 As part of the development of the AMPH ER TAB, the palatability was assessed using a protocol that placed emphasis on several acceptance factors considered important to FDA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, instruments have been developed to assess patient and/or caregiver acceptability of drug regimens. 23 Palatability as an adherence factor has traditionally focused on pediatric patients, generally in antibiotic development, but research has demonstrated that many of the same acceptability factors that apply to treatments for children also apply to adult patients. 16 As part of the development of the AMPH ER TAB, the palatability was assessed using a protocol that placed emphasis on several acceptance factors considered important to FDA.…”
Section: Discussionmentioning
confidence: 99%
“…A threshold of 80% of acceptance (e.g., acceptability score of 1 or 2) in the population examined is the current standard requirement [ 8 ]. A more patient- and caregiver-centred questionnaire (Paediatric Oral Medicines Acceptability Questionnaire) has recently been developed [ 9 ]. The questionnaire is yet to be validated but can be used in drug development to assess the acceptability of oral formulations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more patient- and caregiver-centred questionnaire (Paediatric Oral Medicines Acceptability Questionnaire) has recently been developed [ 9 ]. The questionnaire is yet to be validated but can be used in drug development to assess the acceptability of oral formulations [ 9 ]. We can expect further work in this area in search of the best methodology [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations